Transient Workspaces: Technologies of Everyday Innovation in Zimbabwe - Mavhunga (MIT Press, 2014)
Monograph
fulltext
Keywords: General Topics for Engineers; Communication, Networking and Broadcast Technologies; Computing and Processing; Components, Circuits, Devices and Systems